Analisis Sifat Fisika Tanah Terhadap Infiltrasi Dan Perkolasi Air Di Lahan Pertanian - Mendrofa, Bidcar Ridoan; Telaumbanua, Seveti; Lase, Herni Susanti Putri Sukartini (Jurnal Ilmu Pertanian dan Perikanan, 2024)
This research aims to analyze the influence of soil physical properties on water infiltration and percolation on agricultural land. The method used includes taking soil samples from various locations, followed by analysis of the soil's texture, structure, porosity and density. Infiltration rate was measured using an infiltrometer, while percolation was tested using the percolation method. The results show that coarse textured soil has higher infiltration rates (5 cm/hour) and percolation (3 cm/hour) compared to fine textured soil (2 cm/hour and 1.5 cm/hour). This research confirms the importance of understanding soil physical properties for efficient and sustainable agricultural land management.